Alcalde Distrital y Gobernador Regional - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 2007)
SPANISH: Presentación del Alcalde de Distrito de Punchana Joiner Alberto Vásquez Pinedo y el Gobernador Regional de Loreto Ivan Vasquez Valera.
ENGLISH: Presentation of the Mayor of the District of Punchana Joiner Alberto Vásquez Pinedo and the Regional Governor of Loreto Ivan Vasquez Valera.

SPANISH: Presentación del Alcalde de Distrito de Punchana Joiner Alberto Vásquez Pinedo y el Gobernador Regional de Loreto Ivan Vasquez Valera.
ENGLISH: Presentation of the Mayor of the District of Punchana Joiner Alberto Vásquez Pinedo and the Regional Governor of Loreto Ivan Vasquez Valera.
District Mayor and Regional Governor
Keywords: Iquitos (Perú)|~|Alcaldes y autoridades|~|Perú--Presidentes|~|Perú--Presidentes regionales